SPEAKING IN TONGUES AS EMIGRATION: A SOCIAL-PSYCHOLOGICAL UNDERSTANDING OF TONGUE SPEAKING USING MIGRATION THEORY - Dube, Zorodzai (2012)
In this article, I explore the social function of speaking in tongues using migration theory. My point of departure is that language delimits a community and defines its collective identity. The notion of speaking in tongues is a unique activity in that it is a language done in churches and it is associated with the spiritual world. If the church congregants share a vernacular language outside the church, how do we fathom a phenomenon whereby they speak in a different language when in church? Does not this phenomenon presuppose an inception of a new identity and new space for collective expression? Can we say they are the same people - if not, what has changed? In this article I have developed a hypothesis that speaking in tongues, is at the core of how the church claims an alternative identity different from the larger society. We can describe the mentality as: "we are a heavenly community and we do not belong here on earth." The assumed change of space and identity can be well developed by applying migration theory.
Keywords: Identity; Migration; Place; Space; Tongues